Vroomheid, seksualiteit en maatschappijkritiek - Daan Beekers (Religie & Samenleving)
This article is an ethnographic exploration of the ways in which young, strictly practicing Sunni Muslims and Protestant Christians in the Netherlands deal with issues of sexuality. It is often stated in public debates that the sexual values of Christians, and even more so those of Muslims, diverge from the progressive, secular sexual values that have increasingly come to be taken as the norm. Similar conclusions emerge from existing comparative studies, which are mainly based on quantitative research. However, such research, in which the opinions of religious people are ‘measured’, tells us little about the roles these values play in religious life. Based on my ethnographic research among Sunni and Protestant young adults, my focus in this article is on this lived dimension of values. Discussing the similarities and differences in dealing with issues of sexuality between these groups, I show that, more than my Muslim interlocutors, the young Christians with whom I worked strongly emphasized the theme of sexuality in their attempts at distinguishing themselves from the secular ‘mainstream’.